Evaluation of the Relationship Between Initial Lymphocyte Count and Molecular Response to Imatinib Therapy in Chronic Myeloid Leukaemia Patients - İstemi Serin; Mehmet Hilmi Doğu; Vahit Can Çavdar; Elif Suyani (İstanbul Medical Journal, 2020)

(untitled)
Introduction:Chronic myeloid leukaemia (CML) is a myeloproliferative neoplasm characterised by the overproduction of haematopoietic cells in the granulocytic series, involving translocation of chromosomes 9 and 22. The first tyrosine kinase inhibitor, imatinib, used in the treatment of CML, represents one of the most successful targeted therapies marking a new era in the treatment of CML. Many scoring systems such as the Hasford and Sokal systems have been developed to stratify CML patients into risk categories, and to predict patient outcome. We aimed to evaluate the relationship between blood lymphocyte count (BLC) at diagnosis and molecular response to imatinib therapy as a prognostic factor.Methods:A total of 108 chronic phase CML patients diagnosed between January 2010 and January 2020 were evaluated. Patient characteristics, laboratory results, BLC and response to treatment were recorded.Results:The median BLC was 4,665/mm3 and patients were divided into two groups according to the median BLC as ≤4,665/mm³ and >4,665/mm³. The responses at 3, 6, 12 month and the final status of patients, namely achievement of major molecular response or not, did not differ between the two groups of patients.Conclusion:The introduction of new therapeutic options in CML necessitates improvement in existing risk scoring systems. No direct relationship was found between the initial BLC and imatinib response in CML. However this is the first study exploring the role of BLC at diagnosis in CML patients receiving imatinib, and further studies that look into lymphocyte subgroups as well as bone marrow lymphocyte count at diagnosis might allow a more precise evaluation about the contribution of lymphocyte count to risk assessment in CML patients.